Malolactic fermentation induced by Lactobacillus plantarum in Malbec wines from Argentina - Lerena, María Cecilia; Sari, Santiago Eduardo; Mercado, Laura Analia; Krieger-Weber, Sibylle; Combina, Mariana; Rojo, María Cristina (2017)
The current market requirements to obtain wines with enhanced complexity and varietal character propose the finding of new microorganisms capable of driving the malolactic fermentation (MLF) and contributing to new and distinctive sensory profiles in wines. During MLF, malic acid naturally present in the must is converted into lactic acid by a decarboxylation reaction driven by lactic acid bacteria. Recently, a new strain of Lactobacillus plantarum suitable for MLF in high-pH wines was selected. This study evaluates the capacity of the L. plantarum V22 starter culture to complete MLF at laboratory and semi-industrial scale in different Malbec musts from Argentina. Malbec musts were co-inoculated with S. cerevisiae D254 and L. plantarum V22 to conduct alcoholic fermentation and MLF respectively. Two groups of Malbec musts were identified according to the ability of L. plantarum to consume malic acid. A first group, called “High Feasibility for MLF”, is characterised by the high viability of L. plantarum and the completion of MLF. On the other hand, a second group was identified, termed “Partial Feasibility for MLF”, and is characterised by a decreased viability of L. plantarum and incomplete MLF. This study shows that the capacity of L. plantarum to conduct MLF in Malbec musts is dependent on must composition, further suggesting that the evolution of pH during the fermentation process, rather than initial pH, is a critical factor affecting the successful completion of MLF